Space, place and identity in Kate Chopin's The Awakening - Vidal, Celina M. (2006)
The Awakening was written and published at the end of the nineteenth century. Kate Chopin, the author, was severely criticized for depicting a sexualized and independent-thinking woman who questions her role within the southern patriarchy. Rediscovered in the 1960s by American critics, The Awakening finally gained the recognition it deserves. The novel revolves around Edna Pontellier, a southern mother-wife who starts to realize there is more to womanhood than she had imagined or known. Grand Isle and New Orleans (state of Louisiana, U.S.A.) are the locations where Edna’s transformation unfolds. In such a multi-cultural background (American, southern, Creole, French, Spanish) she embarks upon a trip of exploration, self-discovery, truth and realization in order to find her own place in the world. The aim of this paper is to explore Edna Pontellier’s character and the role played by the geographical, social and human environment in the definition of her identity. In the attempt we will make references to Edna’s personality, her relation with the sea, her awakening self, the lack of space she experiences, the search for a place of her own, the influence of the surrounding communities, her relationship with men and her suicide.